2019
DOI: 10.2144/fsoa-2019-0094
|View full text |Cite
|
Sign up to set email alerts
|

Biosynthesis of Long Chain Base in Sphingolipids in animals, Plants and Fungi

Abstract: Long chain base (LCB) is a unique building block found in sphingolipids. The initial step of LCB biosynthesis stems from serine:palmitoyl-CoA transferase enzyme, producing 3-ketodihydrosphingosine with multiple regulatory proteins including small subunit SPT a/b and orosomucoid-like protein1-3. 3-Ketodihydrosphingosine reductase and sphingolipid Δ4-desaturase, both of them poorly characterized mammalian enzymes, play key roles for neurological homeostasis based on their pathogenic mutation in humans. Ceramide … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 89 publications
0
32
0
Order By: Relevance
“…PHS influences the composition of sphingolipid metabolites in the next steps of SPT was further investigated. Transcription of alkaline ceramidase ( ACER3 ), which hydrates unsaturated ceramides, dihydroceramides, and phytoceramides to form LCBs such as PHS or sphingosine (Mashima et al, 2020), was effectively elevated, by approximately 63%, after 48 h of PHS treatment compared to that after Ppn inoculation (Fig. 6E).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…PHS influences the composition of sphingolipid metabolites in the next steps of SPT was further investigated. Transcription of alkaline ceramidase ( ACER3 ), which hydrates unsaturated ceramides, dihydroceramides, and phytoceramides to form LCBs such as PHS or sphingosine (Mashima et al, 2020), was effectively elevated, by approximately 63%, after 48 h of PHS treatment compared to that after Ppn inoculation (Fig. 6E).…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, sphingolipid metabolites have recently drawn attention as second messengers for stomatal closure, programmed cell death (PCD), and defense against pathogen attack in response to abiotic and biotic stresses in plants (Markham et al, 2013; Magnin-Robert et al, 2015; Glenz et al, 2019). Although the physiological roles of sphingolipid have been extensively studied in animals (Mashima et al, 2020), it remains unclear what mechanism is responsible for their physiological action in plants.i…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, phytosphingosine has a hydroxyl group in carbon C4 from the sphingoide large chain, whilst sphingosine and ceramide contain a trans double bond between C4=C5 [87]. Phytosphingosine has been reported in microorganisms, yeasts, plants, fungi, and mammal cells as an essential component of the membrane, playing key roles in cell growth, survival and cell death, and mediating the response against stress as secondary messengers [92][93][94][95]. In plants, it has been reported that phytosphingosine participates in plant stress signaling through crosstalk-regulated events [96], and it has been also found that this compound obtained from wheat root exudates displays anti-fungal activity on the rhizosphere microbial community associated with watermelon [97].…”
Section: Phytosphingosinementioning
confidence: 99%
“…Emerging evidence demonstrates that LysoGb3 detected in the urine and plasma contains some variant substances [13]. Although the biosynthesis mechanism of LysoGb3 remains to be fully characterized, it is commonly accepted that LysoGb3 is generated from the enzymatic reaction of serine:palmitoyl transferase, a rate-limiting enzyme for sphingolipid biosynthesis [14]. In this case, long chain base (LCB), a building block of sphingolipids, is d18:1 representing a C18 aliphatic lipid with a double bond between C4-C5 with trans geometry and two hydroxyl groups.…”
Section: Lysogb3mentioning
confidence: 99%